Cyclic nonlinear modeling of severely damaged and retrofitted reinforced concrete structures - Markou, George; Mourlas, Christos; Garcia, Reyes; Pilakoutas, Kypros; Papadrakakis, Manolis (My University, 2019)
Advanced numerical methods for seismic assessment of existing substandard reinforced concrete (RC) structures have significantly evolved in the last two decades. Nonetheless, existing numerical tools have numerous limitations (e.g. numerical instabilities, applicable only in 1D or 2D problems, computationally demanding, etc.) and lack of objectivity and accuracy in providing robust, numerically accurate and objective solutions. As a result, new numerical approaches are necessary to solve some of these limitations. This paper presents a detailed 3D modelling approach that solves some of the current modeling limitations. The approach is used to predict the experimental results from i) a substandard RC joint with inadequate detailing subjected to cyclic loading, and ii) the same RC joint rehabilitated and retrofitted with carbon fiber reinforced polymer (CFRP) sheets and subjected to cyclic loading. It is shown that the proposed numerical method reproduces the experimental results of both substandard and CFRP retrofitted specimens in a robust and computationally efficient manner. Current research is investigating the behavior of more RC components and full-scale retrofitted structures. This study contributes towards providing engineers and researchers with an advanced analytical tool to study the cyclic nonlinear behaviour of substandard RC structures.
Keywords: RC Joint; Nonlinear analysis; Finite Element Modelling; CFRP strengthening; Deficient structures